2017
DOI: 10.1093/humrep/dex244
|View full text |Cite
|
Sign up to set email alerts
|

Combined androgen excess and Western-style diet accelerates adipose tissue dysfunction in young adult, female nonhuman primates

Abstract: Research reported in this publication was supported by the Eunice Kennedy Shriver National Institute of Child Health and Human Development of the National Institutes of Health under award number P50 HD071836 to C.T.R. and award number OD 011092 from the Office of the Director, National Institutes of Health, for operation of the Oregon National Primate Research Center. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 73 publications
11
41
0
Order By: Relevance
“…Hyperandrogenemia was also associated with an altered pattern of physical activity, with androgen-treated females showing a delay in the usual puberty-associated decline in activity, followed by a more rapid decline later in the study, corresponding to the period when weight gain was observed. Similar to the findings in hyperandrogenized prepubertal animals described above, peripubertal treatment with androgens resulted in impaired lipolysis ex vivo [73]. Basal lipolytic activity was significantly reduced in OM and SC-WAT, while the β-adrenergic lipolytic response was significantly decreased only in SC-WAT (Figure 2).…”
Section: Effects Of Androgens On Female Nhp Metabolismsupporting
confidence: 83%
See 1 more Smart Citation
“…Hyperandrogenemia was also associated with an altered pattern of physical activity, with androgen-treated females showing a delay in the usual puberty-associated decline in activity, followed by a more rapid decline later in the study, corresponding to the period when weight gain was observed. Similar to the findings in hyperandrogenized prepubertal animals described above, peripubertal treatment with androgens resulted in impaired lipolysis ex vivo [73]. Basal lipolytic activity was significantly reduced in OM and SC-WAT, while the β-adrenergic lipolytic response was significantly decreased only in SC-WAT (Figure 2).…”
Section: Effects Of Androgens On Female Nhp Metabolismsupporting
confidence: 83%
“…Adipocytes also appeared to be affected by the combined treatment, with larger visceral adipocytes and increased fatty acid uptake in visceral WAT in the T+WSD group compared to all other groups. Female rhesus macaques exposed to hyperandrogenemia and WSD exhibited an increase in the average size of visceral adipocytes that correlated with greater insulin resistance compared to animals treated with T or WSD alone [72]; [73] (Figure 3). As noted above, certain metabolic effects were often statistically identified as being driven by either diet or androgen in isolation; however, the group receiving both androgens and WSD was often significantly different from all other groups, indicating a more extreme metabolic phenotype when both conditions were present.…”
Section: Interactions Between Androgens and Dietmentioning
confidence: 99%
“…According reported methods (Murugesan et al, 2015; Varlamov et al, 2017), after fixation and dehydration, samples of different intestinal segments and abdominal tissue were embedded (EG1150H, LEIC, Germany) in paraffin wax, sliced (rotary microtome, RM2016, LEIC, Germany) and stained with hematoxylin and eosin in preparation for examination by microscope (S4E, LEIC, Germany), and image analyzer (Image-ProPlus 6.0). For each intestinal sample, 5 villus were selected for Villus height (VH), crypt depth (CD), mucosal thickness determination.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, the present study advances our understanding of the functional and transcriptional response in SC-WAT associated with dynamic changes in fat mass in response to diet-induced obesity and weight loss and expands our previous studies in NHPs [17,18,20,[64][65][66]. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 64%
“…Free fatty acid (FFA) uptake, adipocyte size and lipolysis was conducted as previously described [17,[20][21][22]. For the lipolysis assay,~200-mg SC-WAT explants were placed in M199 media (General Electric Company, Boston, MA, USA) at room temperature and transported to the laboratory.…”
Section: Cell-based Assaysmentioning
confidence: 99%